2018
DOI: 10.2196/mhealth.9856
|View full text |Cite
|
Sign up to set email alerts
|

Development of an mHealth platform for HIV Care: Gathering User Perspectives Through Co-Design Workshops and Interviews

Abstract: BackgroundDespite advances in testing and treatment, HIV incidence rates within European countries are at best stable or else increasing. mHealth technology has been advocated to increase quality and cost-effectiveness of health services while dealing with growing patient numbers. However, studies suggested that mHealth apps are rarely adopted and often considered to be of low quality by users. Only a few studies (conducted in the United States) have involved people living with HIV (PLWH) in the design of mHea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 32 publications
0
71
0
1
Order By: Relevance
“…Other reviews (i.e., Purnomo et al, 2018), reported similar findings, as well. In Europe, for example, PLWH expressed that the even healthcare providers lacked knowledge about HIV (Marent et al, 2018b). Of note, providers in that same study also expressed their concerns regarding technology security features (Marent et al, 2018a).…”
Section: Implications For Research Theory and Practicementioning
confidence: 89%
See 1 more Smart Citation
“…Other reviews (i.e., Purnomo et al, 2018), reported similar findings, as well. In Europe, for example, PLWH expressed that the even healthcare providers lacked knowledge about HIV (Marent et al, 2018b). Of note, providers in that same study also expressed their concerns regarding technology security features (Marent et al, 2018a).…”
Section: Implications For Research Theory and Practicementioning
confidence: 89%
“…Yè et al's (2018) MOS@N intervention consisted of five training modules delivered to community workers on how to engage patients in care. MOS@N featured interactive voice Personal Privacy, Data Privacy, Confidentiality: Some participants expressed they did not trust the security of cloud-based systems and fear these are a threat to the security of their information and data (Marent et al, 2018b) 3. Hightow-Weidman et al 2018No: Not addressed for the study to optimize engagement in care 2019Yes: app delivery language was English and Zulu, lab values were color-coded to easy distinguish abnormal values, and the app language was "simple"…”
Section: Published Interventionsmentioning
confidence: 99%
“…BeYou+, is a mobile phone app [5] that allows users to track their laboratory results, medication, and appointments. Finally, the EmERGE project seeks to develop an mHealth platform to facilitate self-management and communication between those living with HIV and their healthcare team [46].…”
Section: Digital Tools For Tracking and Sharing Personal Health Datamentioning
confidence: 99%
“…A large proportion of the research in Computer-Supported Collaborative Work (CSCW) and Human-Computer Interaction (HCI) has focused on the informational, emotional and social support provided through online forums and social networking sites, in which people living with a condition can share their experiences and expertise with their peers [16,23,[27][28][29]44,49,50,56,70]. This focus on mutual support amongst peers is also mirrored in research focusing on people with HIV, which has shown that people with HIV look for information and advice about their health from a variety of sources, including newsletters, magazines, personal physicians, and friends [26,[46][47][48]62,63,66].…”
Section: Introductionmentioning
confidence: 99%
“…Still other authors noted this dichotomy within their reported results with some participants expressing significant privacy concerns and others stating it to not be an issue [146,147]. While some users expressed such concerns related to collection of highly sensitive-data, such as that related to behavioral health, reproductive health, or HIV status [135,[148][149][150][151], other users who provided such data still reported little unease related to their privacy [139,142,[152][153][154]].…”
Section: Dynamic User Attitudes Toward Privacymentioning
confidence: 98%